Pre-acceptance of fingerprint identification: a case study among department of administration staff versus academic staff in UiTM Pahang, Campus Jengka / Rozita Mengen, Nor Farhana Mohd Azmi and Azwan Shah Aminuddin - Mengen, Rozita; Mohd Azmi, Nor Farhana; Aminuddin, Azwan Shah (2016)
This study is conducted to investigate the pre-acceptance of fingerprint identification system, amongst chosen staff in Universiti Teknologi Mara (UiTM) Jengka, Pahang in recording their work attendance in the future, if management were to pursue the method. The method of recording is yet to be established, although a few other campuses have already done it. The data collection is by questionnaires distribution. Fingerprint identification system was selected among other biometric system devices in some of UiTM campuses due to its affordability, in comparison to other biometric system devices. Reliability also contributes to the selection of the system. Other reason for its selection was it could provide higher security level, eliminate buddy clocking, increase productivity and simplify many aspects of work, improve punctuality, and eliminate physical punch cards thus there will be no recurrence cost. The fingerprint identification system provide benefits to the organization in order to achieve the organization goal. This study will deliver the pre-acceptence of such technology among two sets of staff, differed by job responsiblilties, in UiTM Jengka Pahang. Findings showed non academic acceptance is higher in comparison to the academic staff. ready for change and to introduce the effectiveness of using fingerprint identification compared to using the manual punch card. This study is about time management awareness among UiTM staff that signifies the ability to accept change and new technology in an organization that is complesent with a fully manual clocking system.